Job crafting leading to employee life satisfaction amongst service sector professionals: Can person-job fit be a possible mediator? - Mimi Banerjee; V.N. Giri (IIMB Management Review, 2025)
Drawing on the job demands and resources theory and the spillover effect theory, we test an empirical model examining the association of job crafting dimensions with life satisfaction. The mediating role of person-job fit (PJF) is considered in the relationship. Data were sourced cross-sectionally from 643 employees associated with the Indian IT and ITeS sector across the country. Relevant statistics such as EFA, CFA, and SEM-based modelling were executed. For mediation analysis, bootstrapping was conducted in AMOS. The study’s findings indicate the effect of job crafting dimensions on life satisfaction. It was observed that PJF emerged as a successful mediator of the relationship for all facets of job crafting. The results advance the job crafting theory by empirically testing employee proactivity in the work domain and its influence on overall life satisfaction. The results attest to the notion of the spillover effect. The study’s findings have theoretical and practical implications for occupational psychology and human resource development.